THE IMPACT OF THE INCREASING COOKING OIL PRICE ON THE ECONOMIC STABILITY OF TRADERS AND BUYERS IN INDONESIA: English - Ramadhini Fitri, Azzahra; Yelly Agustiani; M Rendy Gunawan; Nabilah; Retri Actita Sari; Mitra Anggrainy (CV. Era Digital Nusantara, 2023)
An increase in the price of cooking oil is an event that often occurs in Indonesia and can have a major impact on the economies of both sellers and buyers. The purpose of this research is to evaluate the effect of rising cooking oil prices on the economic stability of sellers and buyers in Indonesia. This study uses a qualitative method with a data collection approach through interviews, field observations, and analysis of related documents.